An experience sampling study of organizational stress processes and future playing time in professional sport. Issue 5 (3rd March 2020) - Rumbold, James; Fletcher, David; Daniels, Kevin
ABSTRACT: This study examined the relationships between daily cognitive appraisals of organizational events, affective responses, and coping. In addition, a 5-year longitudinal relationship between coping and performance outcomes at the senior professional level was assessed. Using an experience sampling method, professional academy rugby union players ( N = 39, M age = 17.23 years, SD = 0.87) completed daily diary measures of appraisals, affective responses, and coping over 5 weeks of training. Hierarchical linear modeling revealed that daily cognitive appraisals were related to daily affective responses and coping functions enacted by behaviours, after accounting for a series of within (e.g., time, day, week) and between-person (e.g., personality, key decision-makers) differences. Zero-inflated negative binomial regression revealed that coping related to eliciting support was associated with minutes played at the senior professional level five years later. This study extends theoretical knowledge of the within- and between-person relationships that explain organizational stress experiences. The findings suggest that some coping functions enacted by behaviours may be early indicators of future performance outcomes in professional sport.